Photophysics of detection of explosive vapours via luminescence quenching of thin films: impact of inter-molecular interactions. Issue 37 (9th September 2016) - Shoaee, Safa; Fan, Shengqiang; Burn, Paul L.; Shaw, Paul E.
Abstract : Fluorescence-based detection of explosive analytes requires an understanding of the nature of the excited state responsible for the luminescence response of a sensing material. Abstract : Fluorescence-based detection of explosive analytes requires an understanding of the nature of the excited state responsible for the luminescence response of a sensing material. Many measurements are carried out to elucidate the fundamental photophysical properties of an emissive material in solution. However, simple transfer of the understanding gained from the solution measurements to the solid-state can lead to errors. This is in part due to the absence of inter-molecular interactions of the chromophores in solution, which are present in the solid-state. To understand the role of inter-molecular interactions on the detection of explosive analytes we have chosen dendrimers from two different families, D1 andD2, which allow facile control of the inter-molecular interactions through the choice of dendrons and emissive chromophores. Using ultrafast transient absorption spectroscopy we find that the solution photoinduced absorption (PA) for both materials can be explained in terms of the generation of singlet excitons, which decay to the ground state, or intersystem cross (ISC) to form a triplet exciton. In neat films however, we observe different photophysical behaviours; first, ISC to the triplet state does not occur, and second, depending on the chromophore, charge transfer and charge separated states are formed. Furthermore, we find that when either dendrimer is interfaced with analyte vapour, the singlet state is strongly quenched, generating a charge transfer state that undergoes geminate recombination.